2007
DOI: 10.1080/14017430701400104
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ASAT, CKMB, Troponin-T and mortality after cardiac surgery

Abstract: ASAT and CKMB can be used to exclude but not to diagnose permanent myocardial injury after cardiac surgery. Increased postoperative ASAT in the absence of increased TnT is not associated with worse clinical outcome than after normal postoperative ASAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Six of the mid-term studies [17,[26][27][28]30,31] described the completeness of their follow-up that ranged from 84% to 100%. Table 1 reports the details of the studies included.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the mid-term studies [17,[26][27][28]30,31] described the completeness of their follow-up that ranged from 84% to 100%. Table 1 reports the details of the studies included.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two studies reported on mid-term (!12 months) results [16,17], eight on short-term ( 30 days) results [18][19][20][21][22][23][24][25] and seven on both [13,[26][27][28][29][30][31], with a total of 237 mid-term deaths by any cause in 5119 patients and 296 short-term deaths by any cause in 9703 patients. Six of the mid-term studies [17,[26][27][28]30,31] described the completeness of their follow-up that ranged from 84% to 100%.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other smaller and underpowered studies did not find an independent association [7][8][9]. Early studies showed that AST levels remained normal in the majority of patients after CABG [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This has occurred in part because troponins have superior sensitivity, specificity and prognostic value in this context [2][3][4][5]. However, one contemporary study reported post-operative AST levels independently predicted early and late mortality after CABG [6], but this finding has not been reproduced in other recent studies [7][8][9]. Whether AST levels are related to post-operative complications has not been previously studied.…”
Section: Introductionmentioning
confidence: 95%